RF communication for wireless fieldbus - Zhu, Yongge. (2008)
Fieldbus networks are becoming increasingly popular in industrial computer-controlled systems, allowing field devices like sensors, actuators and controllers to be interconnected at low cost, less wiring, and requiring less maintenance than point-to-point connections.